Web based participatory irrigation management for Tanjung Karang irrigation scheme, Malaysia - Deepak, T.J. (2011)
In this technological and information age, water IS becoming a source of conflict between domestic, industrial, agricultural and environmental use. Since irrigation uses about 70% of the total freshwater withdrawal, irrigation water management is becoming a challenging issue in Malaysia. The Tanjung Karang Rice Irrigation Scheme (T AKRIS) is no exception. Irrigation water management relies more on information for decision making, while good decisions rely on good information. The usefulness of information depends very much on how well it is organized and how easy it is to use and to access. Thus, accessing information through a web based system is an emerging area of computer applications for real-world problems expected to support the decision making process and also promote the participatory irrigation management. In that notion a threetier architecture framework was carefully studied and implemented to create the Web Based Participatory Irrigation Management (WebPIM) model. WebPIM was created to benefit the users to make timely decisions on irrigation water management through internet. It is a comprehensive model framework designed using Visual Studio 2003 and ASP.Net Programming language. It is a user friendly irrigation water management tool for interactive data storing, viewing, analyzing and for accurate decision making by all stakeholders. The results of mathematical models were incorporated into the decision support tool, which can enhance irrigation water management in TAKRIS. WebPIM model was developed to determine the Total Water Use (TWU) for each paddy plot along the tertiary canal in the study area. Since mid season drainage is beneficial for higher yield, the irrigation season can be split into two stages. The WebPIM program can compute the water supply on day to day basis or with a particular stage of growth with specified number of days. The total rice yield for each lot and water depth in the field are fed by the farmers and Water productivity Index (WPI) are calculated by the model. This enhances the participatory irrigation water management for higher water productivity in the near future. The WebPIM model created to calculate the irrigation water was analyzed through SPSS by using paired samples Hest, to confirm the validity of the model. SPSS analysis show high significant level for two modules, hence the results generated from this WebPIM model are acceptable. WebPIM has the ability to provide access to those users with password and internet connection, bridging the digital divide between rural and urban communities. Decisions made by people who have contributed in its making will be better accepted and implemented towards an improved productivity of the land and water.